PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI DASAR PENENTUAN HARGA JUAL PADA PERUSAHAAN KAROSERI KUDA TERBANG MALANG - Mardianto, Totok (Universitas 17 Agustus 1945 Surabaya, 2021)
The need for vehicles, especially cars in Indonesia, has increased from year to year. This is because Indonesia is a developing country and is actively building. The types of vehicles that are in great demand by the public are commercial vehicles which can also be used for personal purposes. The progress of the car body industry in Indonesia has been able to change the types of commercial vehicles into personal vehicles. With the increasing demand for commercial vehicles to become private vehicles. With the increasing demand for these vehicles resulted in the development of the car body industry in Indonesia. This situation resulted in the emergence of competition between the car body industry, the company must carry out calculations or analyzes of the opinions to be obtained and the costs used to obtain these revenues. In this case the placement of the cost of production plays a very important role . In the process of compiling the cost of production , it should be noted that each component must be calculated correctly and properly charged , so that the reliability of the accuracy of the cost of production as cost information is not misleading and can be accounted for . Therefore, it is necessary to calculate the cost of production as the basis for determining the selling price at the Malang Flying Horse Body